The Influence of Downtilt of Antennae Directional Diagrams on the Formation of Mobile Network Cells and Estimation of Electromagnetic Field Intensity - Pocius, R. V. (Elektronika ir Elektrotechnika, 2005)
The possibility of making use of antennas with continually adjustable mechanical and electrical downtilt of directional diagrams in the formation of mobile network cells has been presented in the paper. The quantitative evaluation of the changes in the intensity parameters of the electromagnetic fields generated by the antenna in the near environment has been made using mechanical and electrical downtilt of directional diagrams. Analytical EMF calculation method errors occurring due to inaccurate evaluation of antennas diagrams and their tilting on the vertical plane have been analysed. Ill.7, bibl.6 (in Lithuanian; summaries in Lithuanian, English and Russian).